(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Many people with serious mental illness are challenged doubly. On onehand, they struggle with the symptoms and disabilities that result from thedisease. On the other, they are challenged by the stereotypes and prejudicethat result from misconceptions about mental illness. As a result of both, people with mental illness are robbed of theopportunities that define a quality life: good jobs, safe housing, satisfactoryhealth care, and affiliation with a diverse group of people. Although researchhas gone far to understand the impact of the disease, it has only recentlybegun to explain stigma in mental illness. Much work yet needs to be done to fully understand the breadth andscope of prejudice against people with mental illness. Fortunately, socialpsychologists and sociologists have been studying phenomena related to stigmain other minority groups for several decades. In this paper, we integrate research specific to mental illness stigmawith the more general body of research on stereotypes and prejudice to providea brief overview of issues in the area.